Understanding Text and Context for Productive Reading: an Analysis of Abu Zaid’s Hermeneutics of the Qur’an - Muhammad Yusuf Kasim; Hasyim Haddade (ADDIN, 2021)
This paper describes the thoughts of Nasr Hamid Abu Zaid on the theory of Al-Qur’an interpretation, with a descriptive-analytic analysis. The data were collected from various sources from Nasr’s writings, books, and journals that wrote about Nasr and his thoughts, as well as other sources that had relevance for analysis purposes. Abu Zaid tries to reveal the meaning and significance (magza) which then brings out the meaning of “the ineffable”. In this case, the meaning is represented by the text or in the sense that it lets the text speak about itself. Then, from that meaning, there is a dialogue with the conditions or contexts that surround a reader. Therefore, the meaning is static because it contains historical meaning, and the significance is dynamic in accordance with the horizon of each reader.